Pathophysiological, haemodynamic and prognostic implications of left atrial dysfunction in cardiac amyloidosis and other cardiomyopathies with hypertrophic phenotype. (4th February 2022) - Palmiero, G; Rubino, M; Lioncino, M; Monda, E; Vetrano, E; Verrillo, F; Dongiglio, F; Fusco, A; Cirillo, A; Caiazza, M; Ascione, L; Caso, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND & PURPOSE. Left atrial function (LAF) is a determinant of clinical status and outcome in many cardiac disorders, including cardiac amyloidosis (CA). Aim of this study is to explores the LAF in CA and other cardiomyopathies with hypertrophic phenotype, and its consequences on cardiovascular haemodynamics, right ventricular function and survival. METHODS. We enrolled 50 patients with CA (26 AL and 24 wtATTR) and 75 with hypertrophic phenotype (LVH group) [25 hypertrophic cardiomyopathy (HCM) pts, 25 hypertensive pts (HypCM), and 25 pts with aortic stenosis (AS)]. LAF was analysed using the phasic method [LAEI as reservoir, LAPEF as conduit, LAAEF as active pump and TLAEF as total emptying function; see figure 1] by LA volumes determination. RESULTS. ATTR patients showed higher LA dimensions and impaired reservoir and total LA emptying function (TLAEF) compared to AL without differences LAF. Compared to the LVH group, CA patients showed higher LA dimension with impaired LAF in all phasic parameters, higher LV filling pressures and reduced biventricular function. We further divided CA and LVH patients into four subgroups based on the presence or absence of LA dysfunction (LADys+ for TLAEF values below the median: <50.2%; range 9.3-70.9%]. Among the groups, patients with CA/LADys+ showed worst clinical status, higher pulmonary pressures (sPAP) and lower TAPSE and TAPSE/sPAP ratio values. After a median follow-up of 24 months, 19 patients died from cardiovascular (CV) causes (15 in CA/LADys+ group and 4 in LVH/LADys+). The overall survival free of CV death was 64% in CA/LADys+ and 85% in LVH/LADys+ (4/26) group [log-rank χ2 29.6; p < 0.0001]. A sequential multivariate model was employed to assess whether LAF could predict CV deaths: TLAEF was entered together with established clinical and echocardiographic parameters (NYHA functional class, LAVI, E/Em, sPAP, TAPSE and TAPSE/sPAP ratio). At the final backward analysis, LAVI, TAPSE/sPAP and TLAEF were independent prognosticators of CV death. CONCLUSIONS. LAF is significantly more impaired in CA than LVH group and is associated with worst clinical status, RV dysfunction and higher LV filling and pulmonary pressure. Moreover, LADys is a frequent feature of CA and significantly associated with higher CV mortality. We suggests that LADys in LVH group could results from chronic pressure overload due to LA"s exposure to high LV diastolic pressure (impaired LV compliance). In CA, LADys could also be determined by direct LA infiltration. The pathophysiological result is a progressive LA remodelling with increased LA pressure, consequent backward transmission to the pulmonary venous system and, ultimately, RV dysfunction. TLAEF is parameter of LAF that correlates with increased pulmonary vascular resistance (measured elsewhere with cardiac catheterisation) and RV dysfunction. In CA, it seems promising as marker of the haemodynamic consequences of LADys and CV mortality.